Os deveres instrumentais ante o teste da proporcionalidade - Bertoni Filho, Haroldo Domingos (2017)
The safeguards to the fundamental guarantees are undoubtedly inserted in our normative collection generating effects by all the branches of the law, which includes that touches the taxation. These guarantees serve as a beacon to the tax activity, preventing the committing of excesses that affect systemic stability. Also should not be excluded from the influence of these guarantees the tax ancillary obligations which acts favoring the tax activity by the knowledge of the taxable facts or by the aid to the verification of the compliance. Considering the constitutional protective context, it is verified that sometimes some state actions generates the collision of guarantees, so that some solution must be given to guarantee the systemic coherence and the proportionality test can be a useful tool in this attempt. Thus, the purpose of this paper is to analyze the tax instrumental duties and verify the possibility of using the tool of proportionality test as a way to consider eventual limitations to fundamental rights promoted as a result of the institution of these duties. For this purpose, we adopted as a starting point the theoretical research on the reflection of the fundamental rights presents in the Constitution and in the institution of tax obligations and tax ancillary obligations, as well as the verification of the applicability of the weighting test in relation to these rights